Own experience of the surgical treatment of acute myocardial infarction - A.G. Bitsadze (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate immediate results of the emergency myocardial revascularization in patients with acute myocardial infarction. Materials and methods. During the period from January 2011 to August 2016, 187 patients with acute myocardial infarction (42 (22.5 %)) without ST segment elevation, 145 (77.5 %) – with ST elevation underwent urgent surgery. In all cases, the troponin I was positive, all patients underwent emergency coronary artery bypass within 6 hours after coronary angiography, and in most patients (155.83 %) coronary bypass surgery was performed using a noncardiaplegic technique. In 32 (17 %) patients, coronary bypass surgery was performed on a working heart. Results. In most cases, we used venous grafts for coronary bypass surgery. In 32 patients with stable hemodynamics, the anterior interventricular artery was shunted by the left internal maternal artery. In 103 (55 %) patients, intracoronary shunts were used in the imposition of distal anastomoses. Complete revascularization (at least 3 bypasses) was achieved in 152 (81.2 %) patients. In 32 (17.1 %) patients, stents were implanted in the pre-operative stage in the infarct-dependent artery, but due to the ineffectiveness of this procedure, the patients were operated on. The total number of shunts per patient was 2.7 ± 0.4. The average duration of artificial circulation is 61.0 ± 2.6 min. Hospital mortality in the presented group of patients was 12.2 % (23 patients died, all with ST segment elevation). Conclusions. The procedure of coronary bypass involving artificial heart fibrillation with intermittent aortic clamping and moderate hypothermia is safe in patients with acute myocardial infarction and allows to achieve satisfactory level of mortality.